ERADICATE THE VIRUS BOOT AND PARTITION WITH NORTON UTILITY 5.4 - Adi Sulistyo Nugroho; Soetirto Sadikin, DRS, MA (Jurnal Sistem Informasi, 1996)
Every user wherever located, of course wanted a software that can be used to eradicate a virusboot / partition effectively and efficiently. What is meant by an effective software is an efficientoperation of the software does not require special skills such as programming ketramilan,durable, lightweight and maintenance costs but able to eradicate the virus boot / partitioncompletely. One of the software that can meet all these requirements is the Norton Utility.Hopefully Norton Utility operation instructions described in this paper useful to the userswherever located.